2023
DOI: 10.1227/neu.0000000000002609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mean Cochlear Biologically Effective Dose on Hearing Preservation After Stereotactic Radiosurgery for Vestibular Schwannoma: A Retrospective Longitudinal Analysis

Abstract: BACKGROUND AND OBJECTIVES: Stereotactic radiosurgery (SRS) is a useful alternative for small- to medium-sized vestibular schwannoma. To evaluate whether biologically effective dose (BEDGy2.47), calculated for mean (BEDGy2.47 mean) and maximal (BEDGy2.47 max) cochlear dose, is relevant for hearing preservation. METHODS: This is a retrospective longitudinal single-center study. Were analyzed 213 patients with useful baseline hearing. Risk of hearing decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Two studies of Tuleasca et al. also showed that BED was associated with linear tumour volume changes and hearing preservation after stereotactic radiosurgery for vestibular schwannomas [9 , 10] . Another study of Tuleasca et al.…”
Section: Methods Detailsmentioning
confidence: 93%
“…Two studies of Tuleasca et al. also showed that BED was associated with linear tumour volume changes and hearing preservation after stereotactic radiosurgery for vestibular schwannomas [9 , 10] . Another study of Tuleasca et al.…”
Section: Methods Detailsmentioning
confidence: 93%
“…Recently, it has been suggested that biologically effective dose (BED) might play a role in various treatment condition outcomes after SRS, more relevant as compared with the classically prescribed physical dose [ 44 ]. Previous studies have underlined a key role in pain relief related to trigeminal neuralgia (TN) [ 38 ], hearing preservation in the context of vestibular schwannomas (VS) [ 4 , 41 , 42 ], biological cure in secreting pituitary adenomas (PA) [ 10 , 15 ], or obliteration of arteriovenous malformations (AVM) [ 28 , 39 ].…”
Section: Introductionmentioning
confidence: 99%